Pelatihan Pembuatan CV Yang Menarik Menggunakan Aplikasi Canva Pada SMK Muhammadiyah 3, Tangerang - Ratna Sari Dewi; Nopi Dwi Lestari; M. Rizky Febriansyah; M. Faizal; Dhea Amalia Putri; Leni Susanti; Dendi Sunardi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Usually applying for a job one has to prepare supporting documents, one of which is a CV or Curiculum Vitae. However, in this globalization era, people usually make CVs as attractive as possible to attract users to continue to the next stage. Therefore, many people use platforms, applications or websites that can make an attractive CV, one of which is the Canva application. Canva is a graphic design application used to create social media graphics, presentations, posters, documents and other visual content. This application provides a variety of design examples to use. Canva consists of two types of services, namely free and paid. For paid services, Canva provides Canva Pro and Canva for Enterprise. In addition, users can also pay for products physically to be printed and shipped. Muhammadiyah 3 South Tangerang Vocational School, which was established on July 1 2009, has two Department Programs, namely Business Management with Accounting Skills Competency and Informatics Technology with Computer Network Engineering Skills Competency. Because of this, we hope that this training on making CVs can help friends at school to make CVs and later can be used to apply for jobs when friends have graduated from the Vocational School.